Immune Profiling Enables Stratification of Patients With Active Tuberculosis Disease or Mycobacterium tuberculosis Infection. (16th October 2020) - Duffy, Darragh; Nemes, Elisa; Llibre, Alba; Rouilly, Vincent; Musvosvi, Munyaradzi; Smith, Nikaïa; Filander, Elizabeth; Africa, Hadn; Mabwe, Simbarashe; Jaxa, Lungisa; Charbit, Bruno; Mulenga, Humphrey; et al.
Abstract: Background: Tuberculosis (TB) is caused by Mycobacterium tuberculosis ( Mtb ) infection and is a major public health problem. Clinical challenges include the lack of a blood-based test for active disease. Current blood-based tests, such as QuantiFERON (QFT) do not distinguish active TB disease from asymptomatic Mtb infection. Methods: We hypothesized that TruCulture, an immunomonitoring method for whole-blood stimulation, could discriminate active disease from latent Mtb infection (LTBI). We stimulated whole blood from patients with active TB and compared with LTBI donors. Mtb -specific antigens and live bacillus Calmette-Guérin (BCG) were used as stimuli, with direct comparison to QFT. Protein analyses were performed using conventional and digital enzyme-linked immunosorbent assay (ELISA), as well as Luminex. Results: TruCulture showed discrimination of active TB cases from LTBI ( P < .0001, AUC = .81) compared with QFT ( P = .45, AUC = .56), based on an interferon γ (IFNγ) readout after Mtb antigen (Ag) stimulation. This result was replicated in an independent cohort (AUC = .89). In exploratory analyses, TB stratification could be further improved by the Mtb antigen to BCG IFNγ ratio ( P < .0001, AUC = .91). Finally, the combination of digital ELISA and transcriptional analysis showed that LTBI donors with high IFNγ clustered with patients with TB, suggesting the possibility to identify subclinical disease. Conclusions: TruCulture offers a next-generation solution for whole-blood stimulation and immunomonitoring with the possibility to discriminate active and latent infection. Abstract : We tested TruCulture, an immunomonitoring tool, to identify active disease from latent Mtb infection. TruCulture showed improved discrimination of tuberculosis cases from LTBI as compared with QuantiFERON. Tuberculosis stratification could be further improved by the Mtb Ag:BCG IFNγ ratio.